Research Paper: Synthesis of Bi1-xYxFe0.8Cu0. 2O3 Multiferroic Nanostructure by a Sol-gel Method and Investigating their Structural, Magnetic, and Dielectric Properties - Seyed Ebrahim Mousavi Ghahfarokhi; Maryam Adel (فیزیک کاربردی ایران, 2023)
In this research, first the bismuth ferrite nanostructure doped with Cu = 0.20 was prepared and then, its (Bi1-xYxFe0.80Cu0.20O3) doping with Y = 0.0, 0.05, 0.10, 0.15, 0.20, 0.25, and 0.30 by a sol-gel method at a temperature of 650 ºC and a 1 h were studied.  The structural properties of the samples have been characterized using XRD, FESEM, FT-IR, and EDX. Investigations of the structural properties showed that by increasing the Y percentage, the peaks are broader and partly have disappeared due to their small size. The magnetic and dielectric properties of the samples using the analyses of VSM, and LCR meters have been investigated. Investigations of the magnetic properties showed that by increasing Y content, the sample's ferromagnetic properties gradually increased. So that the saturation magnetism of our work (2.5 emu/g) compared to the work of others (0.85 emu/g) significantly has increased. Also, the substitute of bismuth ferrite with yttrium and copper has led to the change of the site of Fe in the octahedral center of FeO6 and the change of the bond angle in O-Fe-O. It has created an asymmetry in the structure, which has improved the dielectric properties of the samples. The results of the dielectric properties showed that the dielectric constant, dielectric loss and electric conductivity in the samples doped with Y and Cu are more than in samples without doping.